Development of Regulation of Crypto-assets within the European Union - Kohajda, Michael; Kozieł, Michal; Kurtinová, Simona; Cahlík, Martin (Wydawnictwo Uniwersytetu Rzeszowskiego, 2024)
The article analyzes the development of crypto-asset regulation within the European Union, with the primary aim of evaluating the gradual steps leading to the adoption of the Markets in Crypto-Assets (MiCA) Regulation and its impact on the EU’s legal environment. Using a historical-analytical method, the study examines key milestones in regulation, including responses to risks associated with cryptocurrencies, such as money laundering, and their transformation into a comprehensive regulatory framework. The article also assesses the motivations and impacts of MiCA on market stability and legal certainty for users and service providers. The study provides a systematic overview of regulatory development and identifies challenges linked to the implementation of this groundbreaking regulation.

Artykuł analizuje rozwój regulacji kryptoaktywów w Unii Europejskiej, koncentrując się na ocenie kolejnych kroków prowadzących do przyjęcia rozporządzenia MiCA (Markets in Crypto-Assets) oraz jego wpływu na środowisko prawne Unii Europejskiej. Korzystając z metody historyczno-analitycznej, opisano kluczowe etapy regulacji, w tym reakcje na ryzyko związane z kryptowalutami, takie jak pranie pieniędzy, oraz ich transformację w kompleksowe ramy regulacyjne. Artykuł ocenia także motywacje i skutki MiCA dla stabilności rynku oraz pewności prawnej użytkowników i dostawców usług. Dostarcza systematycznego przeglądu rozwoju regulacji i wskazuje wyzwania związane z wdrożeniem tego przełomowego rozporządzenia.
Rozwój regulacji kryptoaktywów w Unii Europejskiej
Keywords: Market in Crypto-Assets Regulation; Crypto-asset; European Union; Bitcoin; rozporządzenie w sprawie rynków kryptoaktywów; kryptoaktywa; Unia Europejska; bitcoin